The Language of Trust in Raya and The Last Dragon Movie (A Discourse Analysis) - Alim Alim (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2023)
This research discusses the language of trust in Raya and the Last Dragon movie based on the trust-repair discourse model established by Fuoli and Paradis. This research aims to describe the trust-repair discourse in Raya and the Last Dragon movie. This research used a descriptive qualitative method. The sources of data in this research are divided into two categories namely movies as primary data and audiovisual sources as secondary data. The data was collected through downloading the movie, watching the movie, reading intensively, and selecting the data, based on communicative action models of Fuoli and Paradis. The data was analyzed by presenting, describing, interpreting, and concluding the data to answer the research question of this research. The result shows that there were 10 data Raya and Sisu in the movie suffers from trust-repair. There are two reasons to trigger Raya's broken trust. Her friend betrays her. Her friend and her people try to steal her village's gem. In this Raya makes her start hard to trust anyone else. She fears something terrible that can happen to Sisu. Therefore, she never trusts other people around her. Sisu sees this. Sisu thinks that such a broken trust will make Raya in trouble. Finally, Sisu tries hard to teach Raya to trust other people. Sisu uses restore neutralizing the negative and emphasizing the positive. They eventually succeed in building Raya's trust in others.